2019
DOI: 10.15294/rainbow.v8i2.32492
|View full text |Cite
|
Sign up to set email alerts
|

Self-Actualization in Main Character’s Life Journey in "The Bell Jar"

Abstract: Self-actualization is term that is commonly used in psychology theories. The term can be simply translated as the full realization of someone’s potential or true self. This study was conducted to analyze the life journey of the main character of The Bell Jar in achieving herself-actualization. The purposes of this study are to describe the character of the main character in The Bell Jar and to describe the main character in achieving self-actualization and how it is portrayed in the novel. This study was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is reported that the main character named Jonas is classified as dynamic character and after he obtained his selfactualization, he became able to recognize his ability, uniqueness and potentials (Rahayuningsih et al, 2019). The third example clarified that the main character called Esther was able to reach her true selfactualization stage after fulfilling her previous stages successfully (Farid, 2019). The next example is a research that focused on Jane Eyre's self-actualization.…”
Section: Introductionmentioning
confidence: 96%
“…It is reported that the main character named Jonas is classified as dynamic character and after he obtained his selfactualization, he became able to recognize his ability, uniqueness and potentials (Rahayuningsih et al, 2019). The third example clarified that the main character called Esther was able to reach her true selfactualization stage after fulfilling her previous stages successfully (Farid, 2019). The next example is a research that focused on Jane Eyre's self-actualization.…”
Section: Introductionmentioning
confidence: 96%
“…It also symbolizes the vast gap between "writing" and "typewriting", the former being the ambition of many women of Plath"s time while the latter was the societal role imposed on them. Farid and Yuliati (2019) trace the course of Esther"s life as a journey in "self-actualization" by applying Marslow"s Needs Theory and the New Criticism Theory. Ghandeharion et al (2016) rightly calls The Bell Jar "a mirror of American fifties" in tracing the history of disillusionment and identity crisis in the life of Esther Greenwood.…”
Section: Introductionmentioning
confidence: 99%